Using fNIRS to examine occipital and temporal responses to stimulus repetition in young infants: Evidence of selective frontal cortex involvement. (February 2017) - Emberson, Lauren L.; Cannon, Grace; Palmeri, Holly; Richards, John E.; Aslin, Richard N.
Abstract: How does the developing brain respond to recent experience? Repetition suppression (RS) is a robust and well-characterized response of to recent experience found, predominantly, in the perceptual cortices of the adult brain. We use functional near-infrared spectroscopy (fNIRS) to investigate how perceptual (temporal and occipital) and frontal cortices in the infant brain respond to auditory and visual stimulus repetitions (spoken words and faces). In Experiment 1, we find strong evidence of repetition suppression in the frontal cortex but only for auditory stimuli. In perceptual cortices, we find only suggestive evidence of auditory RS in the temporal cortex and no evidence of visual RS in any ROI. In Experiments 2 and 3, we replicate and extend these findings. Overall, we provide the first evidence that infant and adult brains respond differently to stimulus repetition. We suggest that the frontal lobe may support the development of RS in perceptual cortices.